Material point method for simulating strong mining pressure manifestation in multiple hard roof panels controlled by hydraulic fracturing - Zhang, Xingguo; Xia, Binwei; Xia, Ning; Zhou, Lei; Gong, Tao (Frontiers in Earth Science, 2025)
Ground hydraulic fracturing has emerged as an effective technique for mitigating strong mining pressure manifestations in longwall top coal caving (LTCC). However, the influence of different hydraulic fracture types on the strength characteristics of hard roofs (HR) remains unclear, as does their impact on the fracture process and stress redistribution characteristics of HR. In this study, a numerical simulation tool based on the material point method (MPM) and a strain-softening model was employed to construct a model for LTCC involving overburdened multi-layer HR panels. Furthermore, LTCC mining simulation research was conducted, encompassing prefabricated horizontal hydraulic fracturing, vertical fracturing, and non-fracturing models. The results revealed the following: 1) The fundamental mechanism of HR fracture involves tensile failure induced by the gravity load of the overburdened rock layer when suspended. Vertical cracks resulting from surface hydraulic fracturing significantly diminished the tensile strength of HR, thereby greatly reducing its collapse step distance. 2) In LTCC, the stress transfer dynamics within rock layers were characterized by the following: horizontal stress concentrated in the middle through bending deformation of the rock layer upon suspension. Furthermore, upon reaching its peak, the rock layer fractured and collapsed, thereby releasing horizontal stress. Hydraulic fracturing-induced reduction in HR tensile strength effectively mitigated horizontal stress concentration. 3) Vertical stress concentration occurred through the collapse of lower rock layers and the pressure exerted by suspended upper rock layers. The appearance of its peak represents the collapse of multiple rock layers, and through hydraulic fracturing, the collapse step distance was effectively shortened, weakening the concentration of vertical stress.